The Exploring the Role of Halal Literacy Against Interest in Buying Halal Products: Case Study of Change Materials Colloid Concepts on Science Classrooms - Al Zahro, Rd Indah Rofi'ah; Agustina, Tri Wahyu; Cahyanto, Tri (Perhimpunan Intelektual Muslim Indonesia, 2025)
The research aims to explore the role of halal literacy in increasing interest in purchasing halal products, with a focus on understanding changes in material properties and the concept of colloids in science class. The research issue is how integrating halal literacy into science learning can affect students' interest in buying halal products. This research uses a quantitative design with survey methods. The data was collected through a questionnaire given to 125 X-grade students at one of the top preventive schools in the city of Bandung, Indonesia. The students have studied the changes in state of matter and the concept of colloids. Data analysis is carried out using descriptive and inferential statistical techniques to determine the relationship between halal literacy and interest in buying halal products. The research also uses case studies to understand the specific context of teaching in the science classroom. The results of the analysis show that there is a significant positive correlation between halal literacy and interest in purchasing halal products. Students with a higher level of halal literacy tend to show greater interest in purchasing halal products. In addition, an understanding of the concept of colloids and substance changes in science classes also contributed to the improvement of students' literacy. The findings underline the importance of a holistic approach to education, combining science and literacy, to shape consumer awareness and preferences for halal products.